Openness of Existential Temporal Experiences to (Non)Being: The Poetry of Vaidotas Daunys and Valdas Gedgaudas - Jakaitė, Dalia (Colloquia, 2016)
In this article the author analyses the existential experiences typical of the poetry of Vaidotas Daunys and Valdas Gedgaudas, paying particular attention the question of temporality. The author applies the philosopher Juozas Girnius’s explications of the concepts of existential philosophy to the analysis of poems, revealing these as representations of the philosopher’s reflections on theism and atheism, their drama and tragedy. The experiential reality of being and non-being is disseminated in these poets’ works through the existentially symbolic forms of the seasons and (liturgical) time. For Daunys’s poetic subject, the seasons are a means of surviving existential waiting, the presentness of being, the harmonious relationship between nature and humans. In Gedgaudas’s poetry, the dominating images of fall and winter, and other natural signs of the seasons, express the subject’s radical openness to death, the experiences of a collapsed world order, and the loss of eternity. In Daunys’s poetry, prayer and cultural signs infuse time with meaning and point to the experience of a holy You; this expresses the existential hope that it is possible to know the world and oneself. In the paraphrases of liturgical time characteristic of Gedgaudas’s poetry, the relationship of I to the world is marked by unreality and non-existence. Simultaneously, impossible liturgical time also gains a subjectively stronger dimension of presence. The author comes to the conclusion that while being dominates in Daunys’s poetry and non-being prevails in Gedgaudas’s, existential pathos and the poetics of existential discourse connect their work.